1981
DOI: 10.1128/jcm.14.6.674-677.1981
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of a second serogroup of Legionella longbeachae

Abstract: A strain of Legionella longbeachae (Tucker 1) that was isolated from the postmortem lung tissue of a pneumonia patient was serologically distinct from four other strains of L. longbeachae. The recognition of a second serogroup of L. longbeachae represents the first reported instance of serogroup diversity within a species of Legionella other than L. pneumophila. The disease caused by the Tucker 1 strain does not seem to be readily distinguishable from that of pneumonia caused by other legionellae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…logical techniques. This practice has led to the identification and description of serologically distinct strains of the same species (Bibb et al 1981;Tang et al 1984;Thacker et al 1985;WiIkinson et al 1985;Benson et al 1988). Strain ML76 was isolated from an environmental source and presumptively identified as a legionella by its nutritional requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…logical techniques. This practice has led to the identification and description of serologically distinct strains of the same species (Bibb et al 1981;Tang et al 1984;Thacker et al 1985;WiIkinson et al 1985;Benson et al 1988). Strain ML76 was isolated from an environmental source and presumptively identified as a legionella by its nutritional requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Although definitive identification of legionellas can be made only by DNA/DNA homology studies, most newly isolated strains are presumptively identified by nutritional, biochemical and, particularly, serological characteristics. Serological diversity is frequently seen within species, however, and at present L. pneumophila comprises 14 serogroups (Benson et al 1988), and L. bozemanii, L. feeleii, L. hackeliae and L. longbeachae each comprise two serogroups (Bibb et al 1981;Tang et al 1984;Thacker et al 1985;Wilkinson et al 1985).…”
mentioning
confidence: 99%
“…L. longbeachae infection was first described in 1981 among adults with pneumonia in California and Georgia, USA . This species has subsequently been recognized as a cause of Legionnaires' disease in many other locations, including Canada, Europe, Israel and east Asia .…”
Section: Discussionmentioning
confidence: 99%
“…Publications on clinical and epidemiological features of L. longbeachae infection are limited to case reports and small case series . Moreover, cases in these reports were usually diagnosed by culture alone, an approach that may select for more severe disease …”
Section: Introductionmentioning
confidence: 99%
“…Pouco tempo depois, em 1980, foi isolada de um paciente com pneumonia em Long Beach, Califórnia, uma nova espécie de Legionella que foi denominada Legionella longbeachae (McKinney et al, 1981). Um segundo sorogrupo de L. longbeachae foi descoberto durante o mesmo ano (Bibb et al, 1981). Nenhum destes casos relatados de L. longbeachae sugeriu uma fonte conhecida de infecção.…”
Section: Lista De Figurasunclassified